Short and long-term interest rates and the effectiveness of monetary and macroprudential policies - Rubio, Margarita (Elsevier, 2016)
In this paper, I analyze the ability of monetary and macroprudential policies to stabilize both the macroeconomy and financial markets under two different scenarios: short and long-term rates. I develop and solve a New Keynesian dynamic stochastic general equilibrium model that features a housing market, borrowers and savers. Borrowers can access credit markets through their housing collateral. I consider two alternative ways of introducing a macroprudential approach to enhance financial stability: one in which monetary policy, using the interest rate as an instrument, responds to credit growth; and a second one in which the macroprudential instrument is instead the loan-to-value ratio (LTV). Results show that monetary and macroprudential policies are less effective with long-term rates. However, in the short-term case, monetary policy can achieve the financial stability goal only at the expense of higher macroeconomic volatility. If the macroprudential policy is implemented using an LTV rule, financial stability improves significantly with short-term rates but just marginally with long-term ones.